Developing an android-based interactive multimedia tool for improving news writing skills - Hardiana, Maulidia; Risnawati; Sa'adah, Isti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The background of this research is the advancement of technology in the use of intructional media, which helped students overcome the difficulties they experienced in news writing. This study aims to develop an interactive multimedia tool using brainwriting to improve students' news writing skills. The research design was devised as research and development (R&D). This research stage consists of three stages: the first pre-research stage, a needs analysis used to determine the initial conditions for learning, planning, and preparing research instruments. Second, the development stage entailed creating the initial product format, validating the initial product, testing the product, and making the final product revisions. In the meantime, product implementation and distribution were carried out at the implementation stage. Data collection was carried out by expert validation and testing on students. The validation results with experts obtained an average score for the media design aspect 4.4, the graphic aspect 4.5, and the material aspect 4.5. Overall, the average rating is 4.5 in the category of “very good”. Meanwhile, the results of trials on 17 test subjects obtained an average score of 4.4 in the "very good" category. Thus, this interactive multimedia is feasible and can be implemented to teach news writing in class VIII.